Budaya Populer Jepang di Indonesia : Catatan Studi Fenomenologis Tentang Konsep Diri Anggota Cosplay Party Bandung - Antar Venus (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2010)
The research is about self concept in the relations with popular culture, that in the youth cultures has been done since 30 years ago. The term of self concept which becomes focus on this paper was defined by Rogers as how someone see and feel himself. This paper is based on limited introduction research ofphenomenology about self concept of Cosplay Party members in Bandung City. The amount of informants is four and the frequency of interview just twice. The result of the research shows that informants have different background and have positive self concept. They involve in costume player started with their hobby in watching anime and join in Cosplay because of the same of value between them